Dukungan Layanan Penyuluhan Untuk Meningkatan Produksi Benih Lele Dengan Hormon Oodev dan Ovaprim di Desa Sukasari, Kecamatan Cisaat, Sukabumi Jawabarat - Dadang Shafrudin; Wafa Istiqomah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2019)
Sukabumi is one of the freshwater aquaculture production centers in West Java. Among the villages that have potential for fish culture and still need to be developed in are Sukasari Village, located in Cisaat District, Sukabumi, West Java. In this village Catfish (Clarias sp.) is one of freshwater fishes that has important economic value and very good marketing. Therefore its production needs to be improved. The main problem faced is that seed production is still low due to the low frequency of spawning and inadequate environmental stimulation in ovulating eggs. To overcome this, efforts were made to eliminate the constraints of the season in gonadal maturation (eggs) and ovulation through the of extension services support in the dissemination of innovative use of hormones. The material introduced were Oodev to improve quality and promote the development of gonads and Ovaprim to increase ovulation stimulation of fish eggs. Extension activities were conducted in Sukasari Village, Cisaat Subdistrict, Sukabumi, West Java, in the form of lectures and demonstrations on how to use Oodev and Ovaprim in fish breeding. Other material presented was related to increasing consumption of fish and fish processing. Active participants consisted of 13 members of the Kelompok Tani Sejahtera. To find out the response of the participants to the extension activities, questionnaires were distributed. The results showed that injection of ovaprim hormone with a dose of 0.2–0.3 mL / kg of fish weight followed by egg ovulation and fish spawning. While the participants' responses to extension showed agreement on the statement of the importance of extension on hormone use, satisfaction in attending counseling, feeling the benefits of using hormones, affordable hormone prices.